Effect of Vitamin D Supplementation on Bone Mineral Density in Rheumatoid Arthritis Patients With Osteoporosis - Kwon, Oh Chan; Oh, Ji Seon; Park, Min-Chan; Kim, Yong-Gil (Frontiers in Medicine, 2020)
Objectives: To assess the effect of vitamin D supplementation on bone mineral density (BMD) in rheumatoid arthritis (RA) patients with osteoporosis and determine whether supplementation of more than 800 IU/day, which is the currently recommended dose, is beneficial. Methods: RA patients with osteoporosis who received bisphosphonate were included. Patients were classified into four groups according to the dose of vitamin D supplementation (0, 400, 800, and ≥1,000 IU/day). Multivariable linear regression models were performed to evaluate the effect of each dose of vitamin D supplementation on 1-year % change of BMD. Results: In total, 187 RA patients with osteoporosis were included. In the multivariate model adjusted for potential confounders, patients receiving vitamin D supplementation had a significantly higher increase in 1-year % change in lumbar spine BMD (400 IU/day: β=2.51 [95% CI: 0.04–4.99], 800 IU/day: β=2.90 [95% CI: 0.47–5.33], and ≥1,000 IU/day: β=6.01 [95% CI: 3.71–8.32]) and femoral neck BMD (400 IU/day: β=3.88 [95% CI: 1.83–5.94], 800 IU/day: β=4.30 [95% CI: 2.25–6.35], and ≥1,000 IU/day: β=6.79 [95% CI: 4.87–8.71]) than those not receiving the supplementation. Notably, the ≥1,000 IU/day group had a significantly higher increase in 1-year % change in lumbar spine BMD (β=3.11 [95% CI: 0.86–5.37]) and femoral neck BMD (β=2.50 [95% CI: 0.63–4.36]) than the 800 IU/day group. Conclusion: In RA patients with osteoporosis receiving bisphosphonates, vitamin D supplementation was associated with a higher increase in BMD. This effect was higher in vitamin D supplementation dose of ≥1,000 IU/day than in 800 IU/day.